(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Interstitial pneumonia (IP) is characterized by progressive inflammation and fibrosis within the lung interstitium, resulting in altered biochemical homeostasis and structural disruption. Understanding molecular changes is essential for developing targeted treatment strategies. Objective: To investigate the alterations in key biochemical markers — total protein, lactate dehydrogenase (LDH), malondialdehyde (MDA), and alpha-1-antitrypsin (A1AT) — in rat lung tissue during experimental interstitial pneumonia, and to evaluate the therapeutic efficacy of ecdisten, N-acetylcysteine (NAC), and polyoxidonium, individually and in combination. Methods: Interstitial pneumonia was induced in Wistar rats (n=64) via prolonged exposure to tobacco smoke over 60 days. Animals were divided into eight groups: intact, pneumonia control, and six experimental groups receiving monotherapy or combination therapy. Biochemical parameters were assessed in lung homogenates using the Bradford assay, spectrophotometric MDA analysis, LDH activity assay, and immunoturbidimetric A1AT quantification. Results: Compared to intact rats, the pneumonia group exhibited a significant increase in all markers. Therapeutic interventions, especially the triple combination (ecdisten + NAC + polyoxidonium), led to significant normalization of all parameters. Conclusion: Experimental interstitial pneumonia induces pronounced inflammatory and oxidative damage in lung tissue. Combined therapy with ecdisten, NAC, and polyoxidonium demonstrates a synergistic effect in reducing inflammation, oxidative stress, and tissue injury, suggesting a promising strategy for biochemical modulation in pulmonary fibrosis.